2019
DOI: 10.1039/c8mh01241e
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide complexes as molecular dopants for realizing air-stable n-type graphene logic inverters with symmetric transconductance

Abstract: In this communication we have unveiled the importance of lanthanide dopant, to realize n-doping of GFETs with an exceptional ambient stability and enhanced mobility. An unconventional mechanism proposed for such phenomenon is well supported by various analytical methods and rationalized by computational calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…150 Gajarushi, A. S. et al demonstrated logic inverters using graphene FETs. 151 The large-scale integration of 2D MoS 2 FETs was demonstrated recently by Wachter et al by demonstrating a 1 Bit microprocessor. 152 So far, this work has demonstrated the most complex circuit integration using 2D materials while using 115 transistors in a single chip.…”
Section: Two-dimensional Technology State-of-the-art Challenges and W...mentioning
confidence: 95%
See 1 more Smart Citation
“…150 Gajarushi, A. S. et al demonstrated logic inverters using graphene FETs. 151 The large-scale integration of 2D MoS 2 FETs was demonstrated recently by Wachter et al by demonstrating a 1 Bit microprocessor. 152 So far, this work has demonstrated the most complex circuit integration using 2D materials while using 115 transistors in a single chip.…”
Section: Two-dimensional Technology State-of-the-art Challenges and W...mentioning
confidence: 95%
“…Das et al, Tosun et al, Yu et al and and Zhu et al demonstrated logic circuits using WSe 2 FETs and AM demodulator using phosphorene FETs . Gajarushi, A. S. et al demonstrated logic inverters using graphene FETs . The large-scale integration of 2D MoS 2 FETs was demonstrated recently by Wachter et al by demonstrating a 1 Bit microprocessor .…”
Section: Two-dimensional Technology State-of-the-art Challenges and W...mentioning
confidence: 99%
“…The detailed synthetic procedure and crystal structure of 1 were reported by us elsewhere, which is the first air-stable inorganic dopant that stabilizes the N-doping of graphene field-effect transistors with exceptional ambient stability of the device. 30 In the crystal lattice of 1, there are no solvate molecules and the complex is stable up to 350 °C as revealed by thermogravimetric analysis (TGA) reported elsewhere (called the data again in Fig. S1 of the ESI †).…”
Section: Resultsmentioning
confidence: 68%
“…S1 of the ESI †). 30 Furthermore, to check the presence of structural phase transitions, we performed differential scanning calorimetry (DSC) measurements. The DSC curves shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Beyond this, domain 2 (blue, Figure b) is marked by the saturation of the signal response and extends up to pH 2 S of 330 ppb. The observed saturation in the signal from the cCNT corresponds to the saturation of its surface with H 2 S. The Stone–Wales defect centers on the cCNT act as pinning points for the π-electron charge density and hence form the preferred reactive sites.…”
Section: Resultsmentioning
confidence: 99%